The East-West Microwave Radio Relay System – Recollections - Shepherd, Graham (Journal of Telecommunications and the Digital Economy, 2024)
The revisiting of the 1971 paper, ‘The Australian East-West Radio Relay System’, in this issue of the Journal has stimulated this author to recall several of the design challenges encountered with the project in the early 1970s, and the engineering solutions achieved.